2019
DOI: 10.1186/s12879-019-3876-8
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis and HIV-1 viral load in HIV-infected outpatients with immunological failure in Tanzania: a case-control study

Abstract: BackgroundSchistosoma sp. infection has been shown to interact with HIV-1 by modifying susceptibility to the virus and impacting AIDS outcome, but very little is known about the potential impact of Schistosoma sp. infection on the efficiency of antiretroviral treatment (ART) in HIV-1 infected individuals. One study suggested increased immunological failure in patients infected with schistosomes compared to those uninfected. To our knowledge, no report exists on the virological response to ART in schistosome-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…higher viral loads in one [ 98 ], and no significant differences in two [ 90 , 95 ]. Another study reported no difference in viral loads by schistosome status among patients failing first-line ART [ 102 ]. These discrepant results suggest a complex relationship between schistosome infection and HIV-1 viral load that may be influenced by duration of HIV infection.…”
Section: Resultsmentioning
confidence: 99%
“…higher viral loads in one [ 98 ], and no significant differences in two [ 90 , 95 ]. Another study reported no difference in viral loads by schistosome status among patients failing first-line ART [ 102 ]. These discrepant results suggest a complex relationship between schistosome infection and HIV-1 viral load that may be influenced by duration of HIV infection.…”
Section: Resultsmentioning
confidence: 99%